Modern methods of diagnosis of digestive organs - Deekshith Battu (Journal of Science in Medicine and Life, 2024)
Diseases of the digestive system are the most common among all diseases of internal organs. The "area of responsibility" of gastroenterology is the treatment of diseases of the esophagus, stomach, pancreas, intestines, gall bladder and liver. Digestion is a process of mechanical and chemical processing of food, as a result of which nutrients are absorbed and assimilated by the body, and decomposition products and undigested products are removed from it. Digestion is the first stage of metabolism. With food, a person receives energy and all the necessary substances for tissue regeneration and growth. However, proteins, fats and carbohydrates, as well as vitamins and mineral salts contained in food are foreign substances for the body and cannot be absorbed by its cells. These substances must first be converted into smaller molecules that are soluble in water and do not have specific properties. This process takes place in the digestive tract and is called digestion. The causes of indigestion are insufficient separation of gastric juice or a violation of the evacuation of contents due to a pathological process in any organ of the digestive system.